Carving interactions : rock art in the nomadic landscape of the Black Desert, north-eastern Jordan - Østerled Brusgaard, Nathalie, 1989- (Archaeopress Archaeology, 2019)
The Safaitic rock art of the North Arabian basalt desert is one of the few surviving traces of the elusive herding societies that lived there in antiquity. This comprehensive study of over 4500 petroglyphs from the Jebel Qurma region of the Black Desert in North-Eastern Jordan is the first-ever systematic study of the Safaitic petroglyphs.